Indígenas no contexto urbano: identidade, cultura e educação dos indígenas residentes na Comunidade Nações Indígenas Tarumã Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The present dissertation is about the Indians in an urban context, with the purpose of understanding the social and cultural processes of the participants of the research, who live in the city of Manaus in relation to their culture and education. To that end, some questions guided the research: how can we understand, based on the current situation of the natives living in the city of Manaus, it is possible to reflect on how the indigenous culture and the process of school education are being preserved. The methodology adopted was based on bibliographical research, documentary, field research, emphasizing observation. The dissertation is divided into three chapters. The first chapter is made up of the Genesis Partner, a description of the ethnographic historical setting in which the Kokama, the research focus population, emerge, emphasizing the territory-culture and non-indigenous relations in the city of Manaus. This chapter is divided into three sub-topics: 1. Indigenous in the city and Brazilian legislation, 2. Indigenous Rights in the Federal Constitution of 1988, The LDB and the guidelines for the implementation of indigenous schools. The second is centered on the process of Kokoma indigenous migration to the city of Manaus. It is divided into two sub-topics: 1. The process of migration and the organization of communities in the city; 2. The struggle for visibility. 3. Thinking about the historical trajectory, analyzing the setbacks faced by the Kokama and their strength in resisting hegemonic retaliation, it became crucial to seek to understand the motivations, devices, mechanisms and networks of social and cultural relations. What motivated the writing of the third and last chapter is about the indigenous people who live in the urban context, analyzing the so-called "traditional" characteristics and their present cultural aspects, their organization, their political space in the city and their mobilization by reaffirmation of their ethnic identity in the Indigenous Nations Community in the Tarumã neighborhood. Besides explaining the organizations and the leaderships of these people in the city of Manaus, present in the urban societies and the implications present in the process of re-signification of the culture. They are living and what are the ways of preserving culture through the mother tongue.
Indigenous in the urban context: identity, culture, and education of indigenous residents in the Community National Indigenous taruman Manaus.
Keywords: Índios - Migração - Bairro Tarumã-Açu (Manaus); Índios - Manaus (AM); Índios - Educação - Manaus (AM); CIENCIAS HUMANAS: EDUCACAO: FUNDAMENTOS DA EDUCACAO: ANTROPOLOGIA EDUCACIONAL; Contexto Urbano; Migração; Educação